If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6 + -2i)(x + -6 + 2i) = 0 Reorder the terms: (-6 + -2i + x)(x + -6 + 2i) = 0 Reorder the terms: (-6 + -2i + x)(-6 + 2i + x) = 0 Multiply (-6 + -2i + x) * (-6 + 2i + x) (-6(-6 + 2i + x) + -2i * (-6 + 2i + x) + x(-6 + 2i + x)) = 0 ((-6 * -6 + 2i * -6 + x * -6) + -2i * (-6 + 2i + x) + x(-6 + 2i + x)) = 0 ((36 + -12i + -6x) + -2i * (-6 + 2i + x) + x(-6 + 2i + x)) = 0 (36 + -12i + -6x + (-6 * -2i + 2i * -2i + x * -2i) + x(-6 + 2i + x)) = 0 Reorder the terms: (36 + -12i + -6x + (12i + -2ix + -4i2) + x(-6 + 2i + x)) = 0 (36 + -12i + -6x + (12i + -2ix + -4i2) + x(-6 + 2i + x)) = 0 (36 + -12i + -6x + 12i + -2ix + -4i2 + (-6 * x + 2i * x + x * x)) = 0 Reorder the terms: (36 + -12i + -6x + 12i + -2ix + -4i2 + (2ix + -6x + x2)) = 0 (36 + -12i + -6x + 12i + -2ix + -4i2 + (2ix + -6x + x2)) = 0 Reorder the terms: (36 + -12i + 12i + -2ix + 2ix + -4i2 + -6x + -6x + x2) = 0 Combine like terms: -12i + 12i = 0 (36 + 0 + -2ix + 2ix + -4i2 + -6x + -6x + x2) = 0 (36 + -2ix + 2ix + -4i2 + -6x + -6x + x2) = 0 Combine like terms: -2ix + 2ix = 0 (36 + 0 + -4i2 + -6x + -6x + x2) = 0 (36 + -4i2 + -6x + -6x + x2) = 0 Combine like terms: -6x + -6x = -12x (36 + -4i2 + -12x + x2) = 0 Solving 36 + -4i2 + -12x + x2 = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -4i2 + -12x + -36 + x2 = 0 + -36 Reorder the terms: 36 + -36 + -4i2 + -12x + x2 = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -4i2 + -12x + x2 = 0 + -36 -4i2 + -12x + x2 = 0 + -36 Combine like terms: 0 + -36 = -36 -4i2 + -12x + x2 = -36 Add '12x' to each side of the equation. -4i2 + -12x + 12x + x2 = -36 + 12x Combine like terms: -12x + 12x = 0 -4i2 + 0 + x2 = -36 + 12x -4i2 + x2 = -36 + 12x Add '-1x2' to each side of the equation. -4i2 + x2 + -1x2 = -36 + 12x + -1x2 Combine like terms: x2 + -1x2 = 0 -4i2 + 0 = -36 + 12x + -1x2 -4i2 = -36 + 12x + -1x2 Divide each side by '-4'. i2 = 9 + -3x + 0.25x2 Simplifying i2 = 9 + -3x + 0.25x2 Reorder the terms: -9 + i2 + 3x + -0.25x2 = 9 + -3x + 0.25x2 + -9 + 3x + -0.25x2 Reorder the terms: -9 + i2 + 3x + -0.25x2 = 9 + -9 + -3x + 3x + 0.25x2 + -0.25x2 Combine like terms: 9 + -9 = 0 -9 + i2 + 3x + -0.25x2 = 0 + -3x + 3x + 0.25x2 + -0.25x2 -9 + i2 + 3x + -0.25x2 = -3x + 3x + 0.25x2 + -0.25x2 Combine like terms: -3x + 3x = 0 -9 + i2 + 3x + -0.25x2 = 0 + 0.25x2 + -0.25x2 -9 + i2 + 3x + -0.25x2 = 0.25x2 + -0.25x2 Combine like terms: 0.25x2 + -0.25x2 = 0.00 -9 + i2 + 3x + -0.25x2 = 0.00 The solution to this equation could not be determined.
| 120000(x-100)+150((X^2)-400+40000)=22536(600-x) | | 3p-9=180 | | -7(3+6p)+p=12-8p | | -2(d+5)=-4 | | 12y+6=2(6y+1) | | 2(443+88)=56 | | 28+-4x=-64 | | 12x=c+25 | | f(-3)=-2x+3 | | -5(X+3)+2x=45 | | 0.4x-0.8(5-x)=1.4 | | 4x^2-9x+13=8x+9 | | (4a^2-7ab)*2a^3b= | | 3X+9=-4x+25 | | x+(x+200)+3(x+200)=1575 | | C=12x+25findx | | 5(x+5)=-36 | | 3(n-6)+n=4-2(n-1) | | V-9=-10 | | x+(x+200)+3(x+200)=1775 | | 5.2+0.7=2.8+2.2 | | x+(x+200)+3(x+200)= | | -16+y=2y | | 3(z-7)=12 | | 2.49+1.24b=11.17 | | 3g+5=21+g | | 4=-2x+5x+4 | | 3(5)-3x=9 | | 3(2-7)=12 | | 64-2x=75-3x | | 9x+4-5x=-18 | | 8(k-8)=8k-24 |